How Do Pharmacists Construct, Facilitate and Consolidate Their Professional Identity? - Patrick Dawodu; Paul Rutter (MDPI AG, 2016)
The pharmacy profession continues to experience change regarding roles and responsibilities. The supply of medicines still remains a central function, but patient-facing, clinical roles are now becoming more commonplace, where pharmacists use their expert knowledge to maximise patient use of medicines. This transitional state from supplier of medicines to medicines expert raises questions over the contemporary professional identity of pharmacists. This literature-informed commentary highlights the current situation regarding how pharmacists' identity is formed and reinforced. The authors suggest that the profession needs to be clearer in articulating what pharmacy does, and advocate the need for strong branding that the profession, public and other healthcare practitioners understand.